1996
DOI: 10.1042/bj3200309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphatidylethanolamines on the activity of the Ca2+-ATPase of sarcoplasmic reticulum

Abstract: ATPase activities for the Ca(2+)-ATPase of skeletal muscle sarcoplasmic reticulum reconstituted into dioleoylphosphatidylethanolamine [di(C18:1)PE] are, at temperatures higher than 20 degrees C, lower than in dioleoylphosphatidylcholine [di(C18:1)PC], whereas in egg yolk phosphatidylethanolamine the activities are the same as in di(C18:1)PC up to 25 degrees C, suggesting that low ATPase activities occur when the phosphatidylethanol-amine species is in the hexagonal H11 phase. ATPase activities measured in mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…Moreover, the transient presence of such H II phases or other membrane defects may contribute to regulate certain cellular events, such as peripheral protein trafficking, exo-endocytic processes, and vesicle fusion͞fission phenomena. Some recent studies support the involvement of nonlamellar structures, rather than the alteration of other physicochemical properties of membranes, in the control of a number of functions: (i) when PEs are induced to adopt the lamellar phase, G proteins and PKC dissociate from brain cortex plasma membranes (16); (ii) the binding of the insect peripheral protein apolipophorin III to model membranes also appears to be favored by the presence of H II structures (9); (iii) PE species with lower hexagonal phase transition temperature (T H ) values also induce greater increases in G protein binding (this work) and in the PKC activity and binding to membranes (20); and (iv) PEs in the hexagonal phase, but not in the lamellar phase, are able to modulate the Ca 2ϩ -ATPase activity (8). The present study documents an important role of hexagonal-prone lipids (and possibly of H II propensity or H II structures) for signal transduction and other cellular events involving peripheral proteins whose interaction with membranes is regulated by nonlamellar-prone lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the transient presence of such H II phases or other membrane defects may contribute to regulate certain cellular events, such as peripheral protein trafficking, exo-endocytic processes, and vesicle fusion͞fission phenomena. Some recent studies support the involvement of nonlamellar structures, rather than the alteration of other physicochemical properties of membranes, in the control of a number of functions: (i) when PEs are induced to adopt the lamellar phase, G proteins and PKC dissociate from brain cortex plasma membranes (16); (ii) the binding of the insect peripheral protein apolipophorin III to model membranes also appears to be favored by the presence of H II structures (9); (iii) PE species with lower hexagonal phase transition temperature (T H ) values also induce greater increases in G protein binding (this work) and in the PKC activity and binding to membranes (20); and (iv) PEs in the hexagonal phase, but not in the lamellar phase, are able to modulate the Ca 2ϩ -ATPase activity (8). The present study documents an important role of hexagonal-prone lipids (and possibly of H II propensity or H II structures) for signal transduction and other cellular events involving peripheral proteins whose interaction with membranes is regulated by nonlamellar-prone lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PEs with lower lamellar to hexagonal (H II ) phase transition temperature were more effective in increasing this binding, indicating that the presence or propensity to form such nonlamellar structures may play an important role in the G protein association with membranes. Nonlamellar (H II ) lipid structures are required for fusion and fission of lipid vesicles (6,7) and for the activity of certain enzymes (8), but, in general terms, the reason these lipid species are so abundant in natural membranes remains unclear. Interestingly, this mechanism affects not only G proteins, but also other unrelated proteins [protein kinase C (PKC) and the insect peripheral protein apolipophorin III] (9).…”
mentioning
confidence: 99%
“…Here, it has been shown that OA modulated the membrane structure, inducing negative membrane curvature strain (H II -phase facilitation) on PE lipids, whereas the closely related FAs, EA and SA, did not alter markedly the phospholipid bilayer and H II properties. Because the plasma membrane structure regulates a wide variety of cell functions (see above), the present results are relevant to understanding the relationship between membrane structure and function (e.g., 8,24,25).…”
mentioning
confidence: 99%
“…Also, it was shown that nonlamellar lipid structure is induced by signal peptides (16). In particular, such activities as the ATP exchange by mitochondrial proteins (17) and Ca 2ϩ -ATPase activity increase with increasing PE content (18), suggesting importance of nonlamellar structure.…”
mentioning
confidence: 99%